2018
DOI: 10.1097/tp.0000000000001919
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Waiting List BMI Changes on the Short-term Outcomes of Lung Transplantation

Abstract: Our results suggest that obese candidates with an unfavorable pretransplant BMI evolution are at greater risk of worse post-LTx outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Interestingly, after censoring deaths in the year following transplant, survival differences between BMI categories were no longer significant, suggesting that such differences were likely driven by events occurring in the first year after transplant, an observation supported by Lederer et al, who showed that obesity was an independent risk factor for primary lung graft dysfunction [ 17 ]. While the link between high pre-transplant BMI and post-transplant survival appears well evidenced [ 3 , 18 ], this association is much less robust among underweight recipients with reports of no effects [ 19 , 20 ], trends towards increased mortality [ 15 , 21 ] and significant impact on mortality [ 16 , 22 , 23 , 24 ]. Of note, the association between low BMI and increased mortality was mainly seen in the largest cohort studies [ 16 , 22 , 24 ] where it was sometimes restricted to specific subgroups such as underweight recipients with COPD [ 22 ] or manifested not until 1 year after transplant [ 16 ], thereby suggesting different timing and mechanisms for increased mortality in underweight vs. overweight/obese patients.…”
Section: Nutritional Status Of Lung Transplant Recipientsmentioning
confidence: 99%
“…Interestingly, after censoring deaths in the year following transplant, survival differences between BMI categories were no longer significant, suggesting that such differences were likely driven by events occurring in the first year after transplant, an observation supported by Lederer et al, who showed that obesity was an independent risk factor for primary lung graft dysfunction [ 17 ]. While the link between high pre-transplant BMI and post-transplant survival appears well evidenced [ 3 , 18 ], this association is much less robust among underweight recipients with reports of no effects [ 19 , 20 ], trends towards increased mortality [ 15 , 21 ] and significant impact on mortality [ 16 , 22 , 23 , 24 ]. Of note, the association between low BMI and increased mortality was mainly seen in the largest cohort studies [ 16 , 22 , 24 ] where it was sometimes restricted to specific subgroups such as underweight recipients with COPD [ 22 ] or manifested not until 1 year after transplant [ 16 ], thereby suggesting different timing and mechanisms for increased mortality in underweight vs. overweight/obese patients.…”
Section: Nutritional Status Of Lung Transplant Recipientsmentioning
confidence: 99%
“…90 Those with BMI >30 kg/m 2 and obese patients who were unable to lose weight prior to transplant had worse outcomes. 91 Posttransplant nutritional management challenges in these highly catabolic patients were described by Jomphe et al 92 Active casual alcohol use prevalence was about 1 in 3 prior to transplantation and was associated with a 300% increase in mechanical ventilation time and ICU stay and a 150% increase in hospital stay, but mortality and graft function outcomes were not statistically different. 93 E-cigarette use increased in this population.…”
Section: Lung Transplantationmentioning
confidence: 97%
“…With regards the effects of obesity, several studies have demonstrated that a healthy body mass index (BMI) is a predictor of success in lung transplantation . High BMI is associated with a greater incidence of post‐transplant mortality , an increased risk of developing new‐onset diabetes after transplant , and has a negative impact on post‐transplant functional status and quality of life .…”
Section: Review Of the Literaturementioning
confidence: 99%